The prognostic value of serum albumin–globulin ratio in early-stage non-small cell lung cancer: a retrospective study - Wang, Yan (Cancer Manag Res, 2019)
Background: Previous studies demonstrated a significant association between the albumin–globulin ratio (AGR) and various types of cancers. The aim of this study was to evaluate the prognostic value of preoperative AGR in patients with early-stage non-small cell lung cancer (NSCLC). Methods: Patients diagnosed as NSCLC in a single center between January 1, 2014 and February 29, 2016 were retrospectively reviewed. AGR was defined as the ratio between the serum albumin level and the serum globulin level. Receiver operating characteristics analysis was performed to determine optimal cutoff values. Overall survival (OS) and disease-free survival (DFS) were clinical outcomes of our study. Univariate and multivariate Cox regression analyses were used to identify independent prognostic factors, and the Kaplan–Meier method was used to estimate survival curves. Results: A total of 279 early stage NSCLC patients were enrolled in our study with the median follow-up of 39 months (range 1–56 months). The statistical analyses manifested that the age (hazard ratio (HR)=1.045, 95% confidence interval (95% CI): 1.010–1.081, P=0.011) and AGR <1.51 (HR=3.424, 95% CI: 1.600–7.331, P=0.002) were independent prognostic factors for OS; larger tumor (HR=1.211, 95% CI: 1.011–1.450, P=0.038) and AGR <1.51 (HR=2.177, 95% CI: 1.052–4.508, P=0.036) were significantly associated with decreased DFS. Conclusion: The current research reported that the preoperative AGR was an independent prognostic factor for both OS and DFS in early NSCLC, and patients with AGR <1.51 were more likely to have a poor prognosis.